(untitled) (Journal of Science and Technology, 2016)
This work discusses the generation of a quasi monitoring system intended for an operator to change cutting tool during turning operation. The monitoring system uses the effects of turning va riables on acoustic emission signal responses and factorial experimental design approach. In cutting operations, acoustic emission provides useful information concerning the tool wear condition because of the fundamental differences between its source mechanisms in the rubbing friction on the wear land of the single point tool. In this study, effects of cutting speed, feed and tool condition on the acoustic emission signal are investigated using acoustic emission’s energy, amplitude, and frequency response and 23 factorial design for turning operation. Cutting tests were performed using high-speed steel under dry conditions. Calculated effects, standard errors at 95% confidence level, and models governing the acoustic emission response to the cutting conditions have been generated from the acoustic emission signal responses. The generated models revealed that acoustic energy response is affected by significant interactions between cutting speed and feed, and insignificant interactions between cutting speed and tool condition, while the acoustic amplitude response is affected by insignificant interactions among cutting speed, feed, and tool condition. These results suggest that acoustic emission’s energy and amplitude responses could be used to control the cutting speed and feed during turning operation, thus prolonging the life of the cutting tool.